Odpowiedzi

Najlepsza Odpowiedź!
2009-11-23T18:41:55+01:00
A) (x+y+3)*(2x-y)=2x²-xy-2xy-y²+6x=2x²-3xy-y²+6x
b) (3x-1)*(3x+1)*(2-x)=(9x²-1)*(2-x)=18x²-9x³-2+x
c) (3xy-y+3x)*(x-xy+y)=3x²y-3x²y²+3xy²-xy-xy²-y²+3x²-3x²y+3xy=-3x²y²+2xy²+2xy-y²+3x²
d) (2x-(b+a))*((a+b)+2x)=2x(a+b)+4x²-(a+b)²-2x(a+b)=4x²-a²-2ab-b²
e) (x²+4)*(x-2)*(x+2)=(x²+4)(x²-4)=x⁴-16
f) (2x-y)*(2x+y)*(4x²+y²)=(4x²-y²)(4x²+y²)=16x⁴-y⁴
2009-11-23T19:22:00+01:00
A) (x+y+3)*(2x-y)=2x²-xy+2xy-y²+6x-3y
b) (3x-1)*(3x+1)*(2-x)=(9x²-1)*(2-x)=18x²9x(3)-2+x
c) (3xy-y+3x)*(x-xy+y)=3x²y-3x²y²+3xy²-xy+xy²-y²+3x²-3x²y+3xy
d) (2x-(b+a))*((a+b)+2x)=(2x-b-a)*(a+b+2x)=2ax+2bx+4x²-ab-b²-2bx-a²-ab-2ax
e) (x²+4)*(x-2)*(x+2)=(x²+4)*(x²-4)=x(4)-16
f) (2x-y)*(2x+y)*(4x²+y²)=(4x²-y²)*(4x²+y²)=16x(4)-y(4)
|
|
|
takie liczby w nawiasach oznaczają np(4)do potęgi 4
2009-11-23T19:23:22+01:00
A)(x+y+3)*(2x-y)=2x²-xy+2xy-y²+6x-3y=2x²-y²-xy+6x-3y
b) (3x-1)*(3x+1)*(2-x)=(9x²-1)(2-x)= -9x³+18x²+x-2
c) (3xy-y+3x)*(x-xy+y)=3x²y-3x²y²+3xy²-xy+xy²+3xy+3x²-3x²y+3xy=3x²y²+4xy²+6xy+3x²